PREDICTORS OF WORSENING GLYCEMIC CONTROL INDICES AND VARIABILITY AMONG ADMITTED MODERATE TO CRITICAL COVID-19 PATIENTS WITH TYPE 2 DIABETES MELLITUS - Bagos, John Paul Martin; Mendoza, Erick; Matawaran, Bien (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES It has been noted that COVID-19 infection increases the risk of poor blood glucose control in T2DM patients and since diabetes is associated with low-grade chronic inflammation, COVID-19 exacerbates this inflammatory condition leading to heightened insulin resistance and hyperglycemia. Invariably, mortality risk is increased with hyperglycemia and poor glycemic variability, hence, this study aims to identify the predictors associated with glycemic control and variability among patients with COVID-19 and T2DM. METHODOLOGY This is a retrospective cross-sectional analytical study involving 109 patients with the diagnosis of moderate to severe COVID-19 and T2DM. Records review was done from March 2020 to June 2021. Odds ratio from binary logistic regression were computed to determine predictors for worsening glycemic control indices and variability. This research has been approved by the UST Hospital Research Ethics Committee. RESULTS Of the 109 patients, 78% had worsening glycemic control and variability, and 22% had no worsening outcomes. Chronic kidney disease (OR 2.83, p=0.035) was associated with poor glycemic variability. In contrast, increasing eGFR level (OR 0.97, p=0.004) was associated with less likelihood of worsening variability. HsCRP (OR 1.01, p=0.011), HbA1c (OR 1.86, p=0.003), severe COVID-19 (OR 8.91, p=0.008) and critical COVID-19 (OR 4.42, p=0.003) were associated with worsening glycemic control. Steroid use (OR 71.17, p<0.001) showed the strongest association with hyperglycemia. CONCLUSION Potential clinical, laboratory and inflammatory profiles were identified as predictors for worsening outcomes. HbA1c, hsCRP, and COVID-19 severity are predictors of hyperglycemia. Likewise, chronic kidney disease is a predictor of poor glycemic variability.